2018
DOI: 10.1186/s12884-018-1731-3
|View full text |Cite
|
Sign up to set email alerts
|

Where we should focus? Myths and misconceptions of long acting contraceptives in Southern Nations, Nationalities and People's Region, Ethiopia: qualitative study

Abstract: BackgroundDespite its wider benefits and access made at community level, contraceptive methods are one of underutilized services in study area and it is believed to be influenced by misconceptions and socio cultural values. This study was designed to explore women’s perceptions, myths and misconception to inform program implementers.MethodsStudy was conducted in Southern Nations, Nationalities and People’s Region, Ethiopia in 2015. Five focus group discussions with 50 women of reproductive age and 10 key infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 15 publications
9
23
0
1
Order By: Relevance
“…The fear that IUD causes cancer, broids, can get stuck in the uterus discouraged women from using IUD. Studies done in some urban cities in Africa found similar myths like contraceptives can harm your womb and in another study both in Rwanda and Ethiopia mother expressed fear of IUD disappearing in the uterus during sexual intercourse and fear of procedure thus limiting them from taking up family planning especially IUD (19) (20,21). According to our study fear plays a very important part in hindering IUD use.…”
Section: Barriers In Uencing the Use Of Iud Contraceptivesupporting
confidence: 72%
“…The fear that IUD causes cancer, broids, can get stuck in the uterus discouraged women from using IUD. Studies done in some urban cities in Africa found similar myths like contraceptives can harm your womb and in another study both in Rwanda and Ethiopia mother expressed fear of IUD disappearing in the uterus during sexual intercourse and fear of procedure thus limiting them from taking up family planning especially IUD (19) (20,21). According to our study fear plays a very important part in hindering IUD use.…”
Section: Barriers In Uencing the Use Of Iud Contraceptivesupporting
confidence: 72%
“…Prevalence of such myths and misconceptions have also been demonstrated to be existing among young men and women in other studies and national surveys (3,6,10,(16)(17)(18). These studies and national surveys established that the perceived interference with future fertility was the main barrier to modern contraceptive uptake among young women.…”
Section: Discussionmentioning
confidence: 75%
“…Prevalence of such myths and misconceptions have also been demonstrated to be existing among young men and women in other studies and national surveys (3,6,10,(14)(15)(16). These studies and national surveys established that the perceived interference with future fertility was the main barrier to modern contraceptive uptake among young women.…”
Section: Discussionmentioning
confidence: 75%
“…In Kenya, in particular, young people below the age of 25 constitute approximately 66% of the country's population, and often experience some of the poorest sexual and reproductive health (SRH) outcomes (2). The Kenya Demographic and Health Survey (KDHS) of 2014 indicated that 18% of adolescent girls aged [15][16][17][18][19] were already mothers or were pregnant with their first child (3). Childbearing was reported to begin early in Kenya with almost one quarter of women giving birth by age 18 and approximately half by age 20 (3).…”
Section: Introductionmentioning
confidence: 99%